Minimally invasive sampling sources for quality and quantity of DNA for telomere length measurement: a review - Abd Rahman, Alia Azwa; Ho, Yu Bin; Nordin, Norshariza; Sin, Eugenie Sing Tan; Abdullah, Rozaini (Faculty of Medicine and Health Sciences, 2022)
Pesticides are known as potential mutagens as their ingredients may prompt mutations, alter chromosomes, and cause deoxyribonucleic acid (DNA) damage. Biomarker is a common tool used to assess health effects and exposure level. This paper reviewed studies from 2010 to 2020 on pesticides exposure and DNA damage. Seven commonly used biomarkers were comet assay parameters, micronucleus (MN), nuclear buds (NBUD), nucleoplasmic bridges (NPB), 8-hydroxy-2-deoxyguanosine (8-OHdG), telomere length, and chromosomal aberrations (CA). The use of these biomarkers was evaluated with their advantages and disadvantages, as well as population exposed. Based on the findings, biomarkers have shown promising results as precursors of DNA damages. The associations between pesticide and DNA damage were equivocal, but most studies showed increment in genetic damages in exposed versus non-exposed population. These biomarkers can serve as predictive marker for risk of initiation and development of cancers or other chronic diseases.